LEXICONS USED IN GENDING OF GENDER WAYANG AT NGABEN CEREMONY IN TAMAN BALI VILLAGE - Komang Gede Samudra Artajaya. W; I Gede Budasi; Made Aryawan Adijaya (Krinok:Jurnal Linguistik Budaya, 2026)
This study aimed to identify the lexicons found in the Gending Gender Wayang in the Ngaben (Balinese cremation) ceremony in Taman Bali Village and to analyze the cultural meanings contained in each of these lexicons. This study employed a qualitative descriptive design with a naturalistic approach. The data were collected from three informants selected through purposive sampling. Data collection were conducted in Taman Bali Village, Bangli Subdistrict, Bangli Regency, Bali, through in-depth interviews and observation. The research instruments used included an interview guide, a smartphone, and a notebook. Based on the results of data collection and analysis, nineteen lexicons were identified in the Gending Gender Wayang during the ngaben ceremony in Taman Bali Village. These lexicons were classified into two types of gending: gending petegak and gending bebatelan. All the lexicons found contain cultural meanings reflected in five core values: the spiritual journey of the soul, spiritual protection, emotional transformation, spiritual purification, and cosmological balance. These findings indicate that the lexicons in Gending Gender Wayang serve not only as linguistic elements but also as representations of the cultural and spiritual values of Balinese society. This study emphasizes the importance of preserving the lexicon in Gending Gender Wayang as an effort to maintain local identity and ensure cultural sustainability in the midst of globalization. Furthermore, this study is expected to contribute to ethnolinguistic research, particularly in cross-cultural studies and efforts to preserve the Balinese language and culture.